Pengaruh Promosi Di Media Sosial Dan Kualitas Pelayanan Terhadap Minat Beli Konsumen Untuk Bergabung Sebagai Member Di Osbond Gym Cempaka Putih Jakarta Pusat - Ardian Rezaldi; Siti Mariam (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to examine and analyze "The Influence of Promotion in Social Media, service quality, and brand image on consumer buying interest to join as a member at Osbond GYM Cempaka Putih, Central Jakarta". The preliminary research data is data from the Osbond Gym. The research data comes from questionnaires distributed to respondents. The sampling method used was purpose sampling. This method uses criteria that have been selected by the researcher in selecting samples. The number of samples that have been selected is 30 people as the research sample because they have met the requirements or criteria. The data analysis techniques used were instrument test, classical assumption test, and hypothesis testing. The results of this study indicate that the promotion variable on social media partially does not have a significant effect on consumer buying interest. Meanwhile, service quality and brand image variables partially have a significant effect on consumer buying interest. Simultaneously, the three independent variables, namely promotion on social media, service quality, and brand image have a significant effect on consumer purchase interest.